Comparing recruitment strategies to engage hard‐to‐reach men who have sex with men living with HIV with unsuppressed viral loads in four US cities: Results from HPTN 078. Issue 9 (2nd September 2021) - Beyrer, Chris; Malone, Jowanna; Baral, Stefan; Wang, Zhe; Rio, Carlos Del; Mayer, Kenneth H.; Batey, D. Scott; Farley, Jason; Gamble, Theresa; Stanton, Jill; Hughes, James P.; Wilson, Ethan; et al.
Abstract: Introduction: There is an urgent need to identify men who have sex with men (MSM) living with HIV with unsuppressed viral loads to prevent transmission. Though respondent‐driven sampling (RDS) is traditionally used for hard‐to‐reach populations, we compare how RDS and direct recruitment (DR) perform in identifying MSM living with HIV with unsuppressed viral loads and identifying MSM with socio‐demographics characteristic of hard‐to‐reach populations. Methods: This is a cross‐sectional analysis among 1305 MSM who were recruited from March 2016 to December 2017 for a case management intervention trial (HPTN 078). We recruited participants across four cities using RDS and DR methods: Birmingham, AL; Atlanta, GA; Baltimore, MD; and Boston, MA. Participants completed a socio‐demographic questionnaire and underwent HIV testing. We compare the proportion of MSM with HIV and unsuppressed viral loads (HIV RNA ≥ 1000 copies/ml) based on recruitment method using Pearson chi‐square tests. We also compare differences in race, income, healthcare coverage, education, sexual orientation, hidden sexuality and comfort with participating in the LGBT community between recruitment methods and perform non‐parametric trend tests to see how demographics change across RDS recruitment waves. Results: RDS recruited 721 men (55.2%) and DR yielded 584 men (44.8%). Overall, 69% were living with HIV, of whom 18% were not virally suppressed. HIV prevalence was higher among those recruited via DR (84%) compared to RDS (58%), p < 0.0001. Twenty per cent of DR recruits were not virally suppressed compared to 15% of RDS, though this was not significant. DR yielded a significantly higher proportion of Black participants and those with less than a high school diploma. The prevalence of low income, no healthcare coverage, bisexuality and hidden sexuality increased across RDS waves. Conclusions: DR was more efficient in identifying MSM living with HIV with unsuppressed viral loads; however, there was a higher proportion of hard‐to‐reach MSM who were low income, lacked health coverage, were bisexual and were not open with their sexuality in deeper waves of RDS. Researchers should consider supplementing RDS recruitment with DR efforts if aiming to identify MSM with unsuppressed viral loads via RDS.